ICT as a Technological Tool for the Development of Language Skills in Second Language University Students - Pizarro Chacón, Ginneth (2013)
This work aimed to make a research and collect information related to the use of ICTs by teachers of language at the School of Literature and Language Sciences (ELCL) of the Universidad Nacional (Costa Rica) and how they incorporate technological tools into the curriculum of their classes. It also provides some ideas on methodological strategies that can be used in the classroom with the use of ICT. To achieve the main objectives of this work, a questionnaire was used to conduct the research from a descriptive point of view, field work, through a qualitative approach. The interpretive/qualitative paradigm, also called phenomenological, naturalist, humanist or ethnographic, was used since it focuses on understanding and interpreting people`s reality, meanings and intention in order to build knowledge. The study takes place in a real context and a questionnaire was applied to 21 ELCL language teachers. The findings revealed that language teachers incorporate technological tools in a few activities in their classrooms; they do not take advantage of their applicability in all class activities. Besides, they really need more training to know, learn, and incorporate these tools in their curriculum, so they will develop an effective teaching and an active learning. This directed researchers to provide a list of recommendations about teaching techniques that will help language teachers improve their skills and incorporate these tools into their teaching strategies.